Tumor necrosis factor α1 decreases mucosal immune and antioxidant response in the midgut of hybrid fish (white crucian carp ♀ × red crucian carp ♂) - Li, Ke‐Xin; Xiong, Ning‐Xia; Huang, Jin‐Fang; Li, Shi‐Yun; Ou, Jie; Wang, Fei; Luo, Sheng‐Wei (Journal of fish biology, 2024)
Tumor necrosis factor α1 (TNFα) is a pleiotropic cytokine involved in immune regulation and cellular homeostasis, but the crucial role of TNFα in fish gut remained unclear. The current study aimed to evaluate the immunoregulatory function of TNFα1 on gut barrier in a novel hybrid fish (WR), which was produced by crossing white crucian carp (Carassius cuvieri, ♀) with red crucian carp (Carassius auratus red var, ♂). In this study, WR‐tnfα1 sequence was identified, and a high‐level expression was detected in the intestine. Elevated levels of WR‐tnfα1 expressions were detected in immune‐related tissues and cultured fish cells on stimulation. The appearance of vacuolization and submucosal rupture was observed in TNFα1‐treated midgut of WR, along with elevated levels of goblet cell atrophy, whereas no significant changes were detected in most expressions of tight‐junction genes and mucin genes. In contrast, WR receiving gut perfusion with WR‐TNFα1 showed a remarkable decrease in antioxidant status in midgut, whereas the expression levels of apoptotic genes and redox responsive genes increased sharply. These results suggested that TNFα1 could exhibit a detrimental effect on antioxidant defense and immune regulation in the midgut of WR.